Identification of Major Capsid Protein as a Potential Biomarker of Grouper Iridovirus-Infected Cells Using Aptamers Selected by SELEX - Yu, Qing (Front Microbiol, 2019)
Biomarkers have important roles in disease pathogenesis, and serve as important disease indicators for developing novel diagnostic and therapeutic approaches. Grouper iridovirus is a nucleocytoplasmic DNA virus, which not only causes great economic losses in mariculture but also seriously threatens the global biodiversity. However, a lack of biomarkers has limited the progress in clarifying iridovirus pathogenesis. Here, we report novel molecular probes, aptamers, for specific identification of biomarkers in grouper iridovirus-infected cells. Aptamers are selected by SELEX, which is a completely different approach from conventional antibody-based methods for biomarkers discovery. Aptamer-based technology is the unique efficient selection for cell-specific target molecules, and helps find out new biomarkers without the knowledge of characteristics of proteins expressed on virus-infected cell surface. With the implementation of a two-step strategy (aptamer selection and biomarker discovery), combined with mass spectrometry, grouper iridovirus major capsid protein was ultimately identified as a potential biomarker of aptamer Q5 for grouper iridovirus infection. The specific interactions of aptamer Q5 and MCP were experimentally validated by several assays, including EMSA, co-localization of fluorescence by LSCM, binding competition tests, and siRNA silencing tests by flow cytometry. This aptamer-based method for biomarkers discovery developed with grouper iridovirus-infected cells could be applicable to other types of virus infection, markedly improve our studies of biomarker discovery and virus pathogenesis, and further facilitate the development of diagnostic tools and therapeutic approaches to treat virus infection.